KONSEP DAN APLIKASI MODEL PEMBELAJARAN BERBASIS EDUTAIMENT DALAM MENUMBUHKAN KREATIVITAS ANAK USIA DINI - Vava Imam Agus Faisal; Mukromin Mukromin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2020)
The topics examined in this theme is how the concept of berbasisedutaimen learning in fostering the potential of creativity can run in either. The process of learning in early childhood is regarded as the gold. A wide variety of learning support cleaner refining its development. The development happens in children can be seen from the growth of creativity in him. Creativity is the activity of the child in learning activities to respond to that. Emergence of learning-based edutaiment is strategic step in developing creativity. Interpretation of eduataiment-based learning has synergy with the pattern of early childhood learning. Learning emphasis edutaiment gives an atmosphere of active and fun for children. Emplementasi-based learning edutaiment sacara consistent thing to do and there is nothing in order for sustainable development of developing creativity in either. Standards of competence of educators was instrumental in optimizing edutaiment-based learning. Educators appropriate competence could run the process of internalization of learning with a wide variety of teaching. Independently, creativity can grow within the children through a fun learning atmosphere. Educators give referrals and seluasnya space for the growing important role early childhood kreativas